Impacts of climate change on water resources availability for agriculture in Nzhelele Area, Limpopo Province - Ndou, Naledzani (My University, 2024)
Many countries worldwide are experiencing climate change associated impacts on their most valuable sectors such as water resources and agriculture, and South Africa is no exception. The impacts of climate change on water resources availability are projected to increase in almost all regions. This will have a devastating impact on agriculture, especially in a semi-arid and water scarce area of South Africa. This study investigated the impacts if climate change on the availability of water resources for agriculture in Nzhelele area, Limpopo Province. The Soil and Water Assessment Tool (SWAT) was used to evaluate the impacts of climate change on future water resources availability. The SWAT model was calibrated and validated using data for the periods 1991-2000 and 2001-2009 using the SWATCUP-SUFI-2 technique. SWAT model was then fed with projected rainfall and temperature data from Conformal Cubic Atmospheric model (CCAM) for the periods 2023-2053 (near future) and 2053–2082 (far future) to simulate future inflows. Crop water requirements (CWR) for selected crops (maize, tomato, groundnuts, and sweet potato) were estimated using the crop coefficient approach for wet season (summer) and dry season (winter) in near future and far future. The CWRs were compared with inflows to evaluate the availability of water to meet future CWRs. The SWAT model performance was evaluated based on evaluation criteria Coefficient of determination (R2), Nash-Sutcliffe efficiency (NSE), percent bias (PBIAS) and ratio of the root mean square error to the standard deviation of measured data (RSR). The model showed good performance statistics of R2 of 0.71, NSE of 0.56, PBIAS of +0.6% and RSR of 0.66. The study findings revealed that simulated inflows will decrease by 28.67% and 48.22% in the near future and far future, respectively, relative to the baseline period 1987-2009. A comparison of inflows and CWR showed that in near future, water requirements for maize, tomato, groundnuts, and sweet potato in wet season will exceeds inflows by 49.54, 10.05, 9.43, and 9.14%, respectively. In the dry season, water requirements for tomato and sweet potato will be higher than inflows by 29.87 and 71.12%, respectively. However, estimated water requirements for maize were 62% lower than inflows in dry season. In far future, water requirements for maize, tomato, groundnuts, and sweet potato in wet season will be higher than inflows by 66.08, 26.9, 27.15, and 37.22%, respectively, and in dry season water requirements for tomato and sweet potato and maize will be higher than inflows by 62.30, 89.42 and 25.87%, respectively. The study concluded that projected inflows will not be able to meet the simulated future crop water requirements in Raliphaswa irrigation scheme under changing climatic conditions.
MESHWR
Department of Earth Sciences
Keywords: Agriculture; UCTD; Climate change; Conformal-Cubic Atmospheric Model (CCAM); SWAT; Water resources